Pengaruh Penyuluhan Terhadap Pemahaman Operasional Kompor Berbahan Energi Alternatif Serbuk Kayu Pada Ukm Bakpao - M. Wijana; Joniarta I.W; Nuarsa M; Triadi A.A.A; Suartika M (JURNAL KARYA PENGABDIAN, 2023)
Roti Bakpau has been very famous from Babakan Village since 2000. The problem faced by artisans is the high cost of kerosene fuel. Bread craftsmen spend an average of 4 liters of kerosene every day at a price of Rp 48000, equivalent to 1 bag of sawdust with a capacity of 30 kg with a maximum price of Rp 5000. The obstacle of using sawdust by craftsmen is not understanding how to use it. The method used is counseling through material delivery, discussion, practice and mentoring. Meanwhile, the evaluation method is carried out through questionnaires conducted before counseling and after counseling using the Likert scale. This activity went smoothly, all participants who attended were very enthusiastic about participating in counseling. Based on the evaluation, there was an increase in participants' understanding of all variables measured. The highest increase in participants' understanding in the preparation and operation of sawdust stoves by 90.00% and the lowest in understanding the calculation of cost reduction by 73.68% with an average increase in understanding of 82.61%